Investigating the "twelfth man" effect in five European domestic football leagues: a Covid-19 induced natural experiment. - Ramchandani, G.; Millar, R. (Journal of Global Sport Management, 2021)
This study examines whether there is a quantifiable change in the magnitude of home advantage (HA) when football matches are contested behind closed doors. The study incorporates the highest divisions of football leagues in England, Germany, Italy, Portugal and Spain. Due to Covid-19 restrictions, 506 fixtures were played without crowds across these leagues during the 2019/20 season. We conducted inter-season analysis comparing HA between the 2019/20 season and the 2018/19 season (when crowds were present). We also conducted intra-season analysis comparing HA between fixtures played with and without crowds during the 2019/20 season. The Italian Serie A and the German Bundesliga were the only leagues where any evidence of a significant decline in inter-season HA (between 2018/19 and 2019/2020) or intra-season HA (between fixtures with and without crowds in 2019/20) was found. Overall, there is insufficient evidence to generalise that the absence of crowds affects HA in football.